From Worlds of Possibles to Possible Worlds: Or, Dionysus and Apollo after Nihilism - A. Segovia , Carlos; Gevorkyan, Sofya (Das Questões, 2021)
Is it possible to simultaneously escape the regime of authoritarian overdetermination distinctive of all modern totalitarianisms and the regime of anarchic underdetermination characteristic, in turn, of all hypermodern nihilisms? To what extent is Nietzsche’s philosophy responsible for having transformed such conceptual polarity in a frozen dichotomy? And to what extent are Heidegger and Deleuze, despite their differences, responsible for having rendered it all the more inescapable with their subtractive thought, which tends to privilege the possible over being? How, then, should we fancy the Otherwise – the otherwise of today’s unworld? Dionysus and Apollo, this paper argues, provide a tool for it in their quality of conceptual personae through whose interplay “elicitation” and “containment” (Roy Wagner) regain their lost reciprocity against any Subject/Object divide. It thus combines a philosophy-of-mythology approach with a neo-structuralist critique of contemporary thought in dialogue with current anthropological theory in an attempt to figure out the minimal structure of any worlding process. Additionally, it engages in a discussion on the nature and limits of cosmopolitics vis-à-vis nihilism’s accomplishment and it underlines the benefits of embracing a rigorously extra-modern type of logic, neither machinic nor demonstrative nor illuminative, but chiastic.